Simultaneous abatement of organics (2, 4-dichlorophenoxyacetic acid) and inactivation of resistant wild and laboratory bacteria strains by photo-induced processes in natural groundwater samples. (1st September 2018) - Alvear-Daza, John J.; Sanabria, Janeth; Rengifo Herrera, Julián A.; Gutierrez-Zapata, Hector M.
Graphical abstract: Highlights: UV lamp and natural sunlight in presence of H2 O2 led to the bacteria inactivation. Coupled system was efficient removing 2, 4-D and wild bacteria in natural well water. Low sunlight irradiation caused a detrimental effect on bacteria inactivation. Photo-Fenton and other photo-induced reactions led to the 2, 4-D and bacteria removal. Abstract: Simultaneous abatement of 2, 4-dichlorophenoxyacetic acid (2, 4-D at 70 µg L −1 ), Escherichia coli and Klebsiella pneumoniae (laboratory and wild strains) cells from real groundwater samples containing natural iron concentrations (∼0.3 mg L −1 ) was studied by addition of H2 O2 (10 mg L −1 ) using a 18-L compound parabolic collector-CPC solar reactor (under natural sunlight irradiation 150, 000 J m −2 ) equipped with a UV-(A + B + Visible) lamp (15 W: UV-B and UV-A intensities were 0.74 and 6.47 W m −2 respectively) powered by a photovoltaic panel. Viability of E. coli K12 and K. pneumoniae laboratory strains at high initial concentrations of 10 6 –10 7 cells mL −1 (followed by DVC-FISH) dropped 4.69 and 2.18 Logs, respectively after 30 min t30W of combined UV-A + B-Visible lamps and sunlight irradiation (SL + UV + H2 O2 ). Moreover, the initial 2, 4-D concentration underwent a strong reduction reaching concentrations below the detection limit after 5 min t30W of SL + UV + H2 O2 treatment. Regarding real wild bacteria strains often present in natural well waters, which were at low initial concentrations, total culturability (initial concentration 10 1 CFU mL −1 ) and viability (initial concentration 10 2 –10 3 cells mL −1 ) reductions were reached after 30 min (t30W ) of combined treatment. Participation of several photochemical and dark events such as photocatalysis (by iron hydro-oxides and other metal oxides naturally present), Fenton and photo-Fenton (by natural dissolved iron), UV-A + B/NO3 −, Dissolved organic matter (DOM)/UV + Vis and UV-B photolysis of H2 O2 are suggested as responsible of simultaneous 2, 4-D abatement and microbial inactivation in natural groundwater samples.